Activating Cannabinoid Receptor 2 Protects Against Diabetic Cardiomyopathy Through Autophagy Induction - Wu, Aiping; Hu, Pengfei; Lin, Jian; Xia, Wan; Zhang, Rui (Frontiers in Pharmacology, 2018)
Cannabinoid receptor 2 (CB2) has been reported to produce a cardio-protective effect in cardiovascular diseases such as myocardial infarction. Here in this study, we investigated the role of CB2 in diabetic cardiomyopathy (DCM) and its underlying mechanisms. HU308 was used for the selective activation of CB2. Bafilomycin A1 was used for the blockade of autophagy and compound C was used to inhibit AMPK signaling. An streptozotocin (STZ)-induced mice model and high glucose (HG)-challenged cardiomyocytes were applied for study. Cardiac function was detected by echocardiography and Western blot for the detection of autophagy-related and its signaling-related proteins. Transmission electron microscopy was used for the analysis of autophagosome number. Cell viability was detected by Cell Counting Kit-8 (CCK-8) and lactate dehydrogenase (LDH) release assays. We found that activating CB2 by HU308 improved cardiac function in DCM as well as cell viability in cardiomyocytes under HG challenge, while the administration of bafilomycin A1 attenuated the protective effects. HU308 enhanced the level of autophagy in the heart tissues from DCM mice as well as cardiomyocytes under HG challenge. HU308 triggered the AMPK-mTOR-p70S6K signaling pathway, while the administration of compound C attenuated the cardio-protective effect of HU308 in cardiomyocytes under HG challenge. In conclusion, we initially demonstrated that activating CB2 produced a cardio-protective effect in DCM as well as cardiomyocytes under HG challenge through inducing the AMPK-mTOR-p70S6K signaling-mediated autophagy.